Enhanced triacylglycerol metabolism contributes to the efficient biosynthesis of spinosad in Saccharopolyspora spinosa - Li Cao; Yangchun Liu; Lin Sun; Zirong Zhu; Danlu Yang; Ziyuan Xia; Duo Jin; Zirui Dai; Jie Rang; Liqiu Xia (Synthetic and Systems Biotechnology)
Triacylglycerol (TAG) is crucial for antibiotic biosynthesis derived from Streptomyces, as it serves as an important carbon source. In this study, the supplementation of exogenous TAG led to a 3.92-fold augmentation in spinosad production. The impact of exogenous TAG on the metabolic network of Saccharopolyspora spinosa were deeply analyzed through comparative proteomics. To optimize TAG metabolism and enhance spinosad biosynthesis, the lipase-encoding genes lip886 and lip385 were overexpressed or co-expressed. The results shown that the yield of spinosad was increased by 0.8-fold and 0.4-fold when lip886 and lip385 genes were overexpressed, respectively. Synergistic co-expression of these genes resulted in a 2.29-fold increase in the yield of spinosad. Remarkably, the combined overexpression of lip886 and lip385 in the presence of exogenous TAG elevated spinosad yields by 5.5-fold, led to a drastic increase in spinosad production from 0.036 g/L to 0.234 g/L. This study underscores the modification of intracellular concentrations of free fatty acids (FFAs), short-chain acyl-CoAs, ATP, and NADPH as mechanisms by which exogenous TAG modulates spinosad biosynthesis. Overall, the findings validate the enhancement of TAG catabolism as a beneficial strategy for optimizing spinosad production and provide foundational insights for engineering secondary metabolite biosynthesis pathways in another Streptomyces.